A fund of syntactic thoughts. Explorations in the Tesnière archive of the BNF - De Santis, Cristiana (Kwartalnik Neofilologiczny, 2026)
In this article, we aim to report on an exploration of the working materials of the French linguist Lucien Tesnière (1893–1954). The article shows that the main idea inspiring the Éléments de syntaxe structurale (1959), namely dependency grammar, first took shape as a way of addressing recurring difficulties observed in translation, due to an overestimation of morphology at the expense of syntax in both language study and teaching.